Pemikiran Teologi Ulama Bugis dalam Tafsir Al-Qur’an Bahasa Bugis - Mursalim Mursalim (Al-Ulum, 2018)
This research tried to explain the interpretation of theological verses in Alquran as the work of Bugis parsons who organized by Indonesian Parsons Council (MUI) of South Sulawesi. They wrote the interpretation of theological verses in Alquran and titled the book Tafsir Bahasa Bugis 30 Juz, by using Bugis language and Lontara (letters to write Bugis language). This research identified the types of anthropomorphism of Alquran interpretation which followed by the Bugis parsons, either they tend to follow Asy’ariyah group, to follow Mu’tazilah group. The research found that in interpreting theological verses into Bugis language, the Parsons of MUI in South of Sulawesi followed the Asy’ariyah group approach. They followed this approach in order to enable the reader to understand the concept of theological in Alquran which believe that God is the only one and He is not the same with His creature. However, in other verses interpretation, they tried to explain the God existence rationally.